Stratification of cephalosporins based on physicochemical and pharmacokinetic variables using multivariate statistical tools. (2024)
Prescription is one of the most important strategies for the treatment of patients, with the objective of managing symptoms and, on occasion, preventing future conditions. Prescribing is a complex exercise that requires diagnostic skills, knowledge of common medications, understanding of the principles of clinical pharmacology, communication skills, and the ability to make decisions based on judgments of potential benefits and risks based on available evidence and specific factors related to the patient being treated. The progressive accumulation of clinical trial data on commonly used drugs would allow the possibility of providing sufficient evidence to support most prescribing decisions. Journal Pre-proof However, physicians generally prescribe under varying circumstances and often in the absence of directly related evidence. Rational prescribing decisions are often based on evidence that must be interpreted in the context of many other factors not found in any clinical trial. (1–4). Considering that the most widely used therapeutic technology is the drug, but in some circumstances, its use can be inefficient, which affects the quality of healthcare, jeopardizes patient safety, and wastes resources. Clinicians are confronted with an everincreasing supply of drugs that exceeds their knowledge of how to use them; therefore, it is necessary to select drugs rationally, based on evidence of efficacy and safety, while seeking the greatest benefit for patients at the lowest possible cost. Medicines can be selected at different levels: health systems, organizations, health centers, and professionals, but they always follow the same criteria. As the drug and its knowledge are constantly changing, drug evaluation and selection must be a continuous and multidisciplinary process. Due to those above, it is pertinent to propose strategies based on multivariate statistical tools, taking into account the capacity of this type of statistics to stratify the different pharmacological alternatives in order to provide less subjective options to the prescribing team. (5,6) A group of drugs frequently used in clinical practice are cephalosporins, which correspond to a type of beta-lactam antibiotics frequently used in medicine due to their high activity against bacteria, proven efficacy, and good safety. These antimicrobials are used as first-choice treatments in various clinical conditions, such as skin and soft tissue infections, intra-abdominal sepsis, diabetic foot infections, acute meningitis, pneumonia, endocarditis, and as prophylaxis in cardiothoracic, orthopedic, abdominal and pelvic surgery. However, they can be used indistinctly without taking into account some possible advantages derived from their physicochemical and pharmacokinetic variables, a situation that, at a given moment, may allow better diffusion to infected tissues. The objective was to look for options to interpret and take advantage of the information related to the physicochemical nature of drugs in order to facilitate decision-making on the choice of pharmacological therapies, trying to select the appropriate alternatives for each case based on their possible kinetics and distribution on the basis of the inherent properties of each substance. (7)